Robotic vs. Standard Laparoscopic Technique – What is Better? - Köckerling, Ferdinand (Frontiers in Surgery, 2014)
Introduction Laparoscopic surgery is subject to certain limitations that can be a problem when performing complex minimally invasive operations. Robotic surgery was developed precisely to overcome such technical limitations. The question therefore arises whether robotic surgery leads to significantly better results compared with standard laparoscopic surgery. Methods Based on comparative systematic reviews and meta-analyses, this paper examines whether the robotic technique when used for abdominal and visceral surgery procedures confers advantages on the patient compared with the standard laparoscopic technique. Results Even for demanding visceral surgery procedures, the perioperative complication rate for robotic surgery is not higher than for open or laparoscopic surgical procedures. In cancer cases the oncological accuracy of robotic resection for gastric, pancreatic and rectal resection is seen to be adequate. Only the operating time is generally longer than for standard laparoscopic and open procedures. But, on the other hand, in some procedures blood loss is less, conversion rates are lower and hospital stay shorter. Conclusion To evaluate the future role of the robotic technique for visceral surgery, high-quality prospective randomized trials are urgently needed.